THE INNOVATION OF MODERN ISLAMIC EDUCATION SYSTEM BASED ON PROGRESSIVE BOARDING SCHOOL IN MADRASAH TSANAWIYAH NEGERI 1 BIMA - herman, Su (Studia Religia, 2018)
AbstractThe purpose of this research is to find out the implementation of the innovationof modern Islamic education system based on the progressive boarding schoolin Madrasah Tsanawiyah Negeri 1 Bima which is able to produce a newapproach that can accommodate all the development of spiritual, emotional,intellectual and social students. Innovation of modern Islamic educationsystem based on boarding school become an alternative strategy of PAI learningwhich able to give hope in teaching moral value for learners. This research is aqualitative descriptive, using sociological phenomenology approach.The resultof this research shows that the innovation of the Islamic education system inthe Madrasah Tsanawiyah Negeri 1 Bima comes from a fundamental thoughtand contains a meaningful reconstruction of the nation for the realization ofthe ideals of the developed, equitable, prosperous, dignified, and sovereignstate parallel to other nations and countries that have achieved excellenceprogressing in the spirit, mindset, behavior and always future oriented torealize better conditions as a result of an innovation.Â Keywords: Innovation in Education, Islamic Education, Boarding School